Design, synthesis and evaluation of MCH receptor 1 antagonists—Part II: Optimization of pyridazines toward reduced phospholipidosis and hERG inhibition. Issue 16 (15th August 2015) - Roth, Gerald J.; Heckel, Armin; Kley, Jörg T.; Lehmann, Thorsten; Müller, Stephan G.; Oost, Thorsten; Rudolf, Klaus; Arndt, Kirsten; Budzinski, Ralph; Lenter, Martin; Lotz, Ralf R.H.; Schindler, Marcus; et al.
Graphical abstract: Abstract: Despite recent success there remains a high therapeutic need for the development of drugs targeting diseases associated with the metabolic syndrome. As part of our search for safe and effective MCH-R1 antagonists for the treatment of obesity, a series of 3, 6-disubstituted pyridazines was evaluated. During optimization several issues of the initial lead structures had to be resolved, such as selectivity over related GPCRs, inhibition of the hERG channel as well as the potential to induce phospholipidosis. Utilizing property-based design, we could demonstrate that all parameters can significantly be improved by consequently increasing the polarity of the compounds. By this strategy, we succeeded in identifying potent and orally available MCH-R1 antagonists with good selectivity over M1 and 5-HT2A and an improved safety profile with respect to hERG inhibition and phospholipidosis.